Elementy rytuału przejścia w „Innym” Jurija Mamlejewa. Prolegomena - Przybysz, Anna Katarzyna (Studia Rossica Posnaniensia, 2016)
This article is an attempt to analyze the category of meeting between two main characters in The Other using a symbolic key. I try to explain the important role of such semiotic categories as threshold and mask in the process of becoming more aware about ourselves, which I interpret as part of the process of rite de passage.